Factors Affecting Guest Expectations towards Housekeeping Services: A Study of Five-Star Hotels of National Capital Region (International Journal of Food and Nutritional Sciences, 2022)
The guest visits to five-star hotels with great expectations. Various factors in Housekeeping department are there which influence the satisfaction level of the guest. This research paper deals with factors affecting guest expectations towards housekeeping. 39 variables of housekeeping service were sorted on the basis of literature review. Upon analysis eight sets were prepared consisting of four factors each. Both primary and secondary data was used.